Co-creation value: From time to time - Barus, Alexander; Martiyanti, Dwi; Sembiring, Hendri; Pakarti, Piji; Fajrillah, Fajrillah (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2023)
This literature review uses a systematic review approach and bibliographic analysis. The data source is google scholar, and the search for article data uses PoP by using the terms: